The Second SSAAPS Annual Conference - SSAAPS Annual Conference 2003 : Lund); The Swedish School of Advanced Asia Pacific Studies; Lund University (Lund : Lund University, 2004)
This cd-rom provides abstract and fulltext of final papers for second SSAPS Annual Conference that listed by author and also by title
Keywords: East Asia -- Economic conditions; Asia Southeastern -- Economic conditions; East Asia -- Political aspects; Asia, Southeastern -- Social